"Un-silencing queer Nigeria" : Representations of queerness in contemporary Nigerian fiction - Akram, Tahzeeb (Rhodes University, Faculty of Humanities, Department of Literary Studies in English)
This thesis analyses contemporary queer Nigerian fiction, particularly queer representations regarding law, religion and culture in Nigeria's heteropatriarchal and queerphobic society. I explore a number of authors' use of different literary forms and platforms to promote and represent non-conforming genders and sexualities in queerphobic Nigeria. These narratives show queer people navigating the heteronormative society vis-Ã -vis marriage, family, intimacy, work, violence and rights activism. I draw on Western and African gender and queer theories for the concepts, definitions and critical terminologies used in this thesis. African queer theorists and activists are highlighted for their reclaiming queer history from among the early records in Africa as well as contemporary queer Nigerian literature and activism. Religion and queerness are crucial themes in Chinelo Okparanta's same sex women's novel, Under the Udala Trees. Using queer African Christian theology against Nigeria's conservative socio-religious setting, I demonstrate that queerness is not a threat to Nigerian's Christian faith, and that mutual coexistence of queer sexuality and Christianity advances queer rights in that society. Nnanna Ikpo's FimÃ SÃláº¹Ì€ Forever: Heaven gave it to me's problematises heteronormative masculinities and the manufacturing of heteropatriarchy and queer masculinities in Nigeria. I examine the protagonists who are both victims of and perpetrators in their queerphobic society. The socio-legal focus I employ examines the impact of the 2014 Same Sex Marriage Prohibition Act on Nigeria's already marginalised and oppressed queer community. There are vast opportunities for queer Nigerian artists to create, publish and promote queer identities in the safe and enabling space of online platforms via physical distancing between the queer community and the queerphobic society. From the digitally published 14: An Anthology of Queer Art's two volumes, five short stories are analysed regarding different forms of intimacies in queer men's relationships. These queer contemporary fiction writers offer complex representations of queerness within Nigeria's heteropatriarchal and queerphobic society that polices non-normative bodies through religion, culture and the law. Such literary texts, digital literary platforms and activism vitally provide queer Nigerians a progressive space to assert queer presence, voices lives and rights to educating and re-socialising their society towards humaneness.
Keywords: Heterosexism in literature; Patriarchy in literature; Homophobia in literature; Sexual minorities in literature; Nigerian literature -- 21st century -- History and criticism; Queer theory -- Nigeria; Gender identity -- Law and legislation -- Nigeria; Gender identity -- Religious aspects; Sexual minorities -- Nigeria -- Social conditions; Nigeria -- Same Sex Marriage (Prohibition) Act, 2013